Політична відповідальність у процесі взаємодії влади та суспільства : комунікативний вимір. - Дунаєва, Г.О.; Дунаева, Г.О.; Dunaeva, G. (My University, 2011)
The article deals with the interpretation of the phenomenon of political responsibility as a communicative process. The basis of political responsibility for such an understanding, not acting government activities, but relationships between citizens and authorities (the concept of «responsible citizen»). Emphasis on the fact that in modern conditions that relationship mediated by the media.
Дунаєва, Г.О. Політична відповідальність у процесі взаємодії влади та суспільства : комунікативний вимір. / Г.О. Дунаєва // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 44 . С. 229 - 236.
Keywords: Політична відповідальність; Взаємодія влади та суспільства в Україні; Державна влада; Государственная власть; Взаимодействие власти и общества в Украине; Политичесская ответственность; Politichesskaya responsibility; The interaction of government and society in Ukraine; government